Pandangan Al-Qur’an Terhadap Fundamentalisme Menggunakan Analisis Tafsir Maudhu’i - Haedarulloh, Ilhaq; Maulana, Ilham; Falasifa Bilqis, Luthfia Halum (Melati Institute, 2024)
The emergence of differences in understanding religion is increasing from time to time. Not a few there are understandings that deviate from the real teachings. This perfect religion is reduced or added for some people because of their inaccurate understanding of religion, so they do unnatural things by using the name of religion as the reason, and make religious identity become tarnished in society because it disturbs the comfort of social life by using religious reasons. Groups that do so are groups that adhere to fundamental understanding or who only understand religion from the point of writing or only textual, without paying attention to cultural customs and circumstances in a particular environment, which makes a bad assessment of religion, which should be rahmatan lil 'alamin. This paper contains how the Qur'an itself views people who are wrong or excessive in doing something using religious reasons. This research was conducted with a descriptive analysis method using the Qur'an and Hadith as primary sources and several related writings as secondary sources.